Structure and electronic properties of amorphous As40Se30S30 films prepared by ion-plasma sputtering method (Physical Sciences and Technology, 2016)
The atomic and local structure, as well as the electrical, optical, photoelectrical properties and drift mobility of charge carriers in amorphous As40Se30S30 films, prepared by the method of RF ion-plasma sputtering (RF-films), were studied in comparison with those of the films, prepared by the method of thermal vacuum evaporation (TE-films). These two methods differ significantly in the conditions of substance vaporization and condensation of atoms on a substrate. It was found that the films fabricated by the different methods have differences in structure and electronic parameters. The essential differences in photoconductivity and transport phenomena are observed, too. It was concluded that RF As40Se30S30 films have a modified structure. This leads to changes in the spectrum of extended and localized electronic states in these films, which, in its turn, causes differences in their electronic properties.
Keywords: Key words; ion-plasma sputtering; RF-films; photoconductivity. PACS numbers; 68.55.-a; 73.61.-r